2012
DOI: 10.1016/j.pneurobio.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1C (Cav1.2) in the pathophysiology of psychiatric disease

Abstract: One of the most consistent genetic findings to have emerged from bipolar disorder genome wide association studies (GWAS) is with CACNA1C, a gene that codes for the α1C subunit of the Cav1.2 voltage-dependent L-type calcium channel (LTCC). Genetic variation in CACNA1C have also been associated with depression, schizophrenia, autism spectrum disorders, as well as changes in brain function and structure in control subjects who have no diagnosable psychiatric illness. These data are consistent with a continuum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
189
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(198 citation statements)
references
References 175 publications
3
189
0
2
Order By: Relevance
“…Indeed, largescale genome-wide association studies (GWASs) revealed a strong association between susceptibility for various psychiatric disorders, including bipolar disease, schizophrenia, and major depression, and single nucleotide polymorphisms (SNPs) in the CACNA1C gene. These are located within intronic regions (Bhat et al, 2012). SNP rs1006737, a common intronic risk haplotype, is one of the most consistent associations in psychiatric genetics (Bhat et al, 2012;Yoshimizu et al, 2015).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, largescale genome-wide association studies (GWASs) revealed a strong association between susceptibility for various psychiatric disorders, including bipolar disease, schizophrenia, and major depression, and single nucleotide polymorphisms (SNPs) in the CACNA1C gene. These are located within intronic regions (Bhat et al, 2012). SNP rs1006737, a common intronic risk haplotype, is one of the most consistent associations in psychiatric genetics (Bhat et al, 2012;Yoshimizu et al, 2015).…”
Section: +mentioning
confidence: 99%
“…These are located within intronic regions (Bhat et al, 2012). SNP rs1006737, a common intronic risk haplotype, is one of the most consistent associations in psychiatric genetics (Bhat et al, 2012;Yoshimizu et al, 2015). It also has an impact on task-based human behaviors and human brain morphology, such as gray matter volume of specific regions (for references, see Yoshimizu et al, 2015).…”
Section: +mentioning
confidence: 99%
“…These voltage-dependent calcium channels have been described to be associated with epilepsy and several neuropsychiatric disorders such as autism and schizophrenia. [1][2][3] Typically, these channels are composed of four subunits: an alpha1, alpha2-delta, beta and gamma subunit, each encoded by several genes. The a 1 subunit is the primary subunit necessary for channel functioning and in total 10 genes are known to encode this subunit.…”
Section: Introductionmentioning
confidence: 99%
“…The L-type calcium channel, Ca v 1.2, plays a central role in regulating an activity-dependent signaling network that is essential for neuronal function [1][2][3][4][5][6]. A particularly salient example of a perturbation in Ca v 1.2 function is Timothy syndrome (TS), a rare genetic disorder caused by dominant mutations in the gene CACNA1C, which encodes the α subunit of the voltage-gated calcium channel Ca v 1.2.…”
Section: Introductionmentioning
confidence: 99%